2023
DOI: 10.1002/npr2.12348
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐focused psychological interventions in women with endometriosis: A systematic review

Abstract: AimsAs a chronic inflammatory disease, endometriosis (EMS) is often associated with pain affecting different aspects of women's lives. Up to now, a wide variety of interventions have been implemented to alleviate pain in patients with this condition, including pharmacological, surgical, and rarely non‐pharmacological ones. Against this background, this review aimed to investigate pain‐focused psychological interventions among EMS women.MethodsA systematic review of the articles published in this field was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the literature, it has been evidenced that pain severity in women suffering from endometriosis was positively associated with subjective psychosocial impairment [ 58 ]. Psychological interventions for the management of pain have been instead documented as efficient [ 59 , 60 ]. The meaning of this literature evidence is that pain, as well as fatigue, has important psychological components that should always be assessed and treated when endometriosis is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been evidenced that pain severity in women suffering from endometriosis was positively associated with subjective psychosocial impairment [ 58 ]. Psychological interventions for the management of pain have been instead documented as efficient [ 59 , 60 ]. The meaning of this literature evidence is that pain, as well as fatigue, has important psychological components that should always be assessed and treated when endometriosis is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have shown improvements in sexual arousal, desire, and satisfaction and reduction in anxiety following mindfulness therapy. Another systematic review by Samami et al [ 17 ] on pain-focused psychological interventions in women with endometriosis showed that cognitive-behavioral therapy, mindfulness, yoga, psychoeducation, and progressive muscle relaxation training were all associated with a reduction in pain, as quantified by the Numeric Rating Scale, Endometriosis Health Profile, Visual Analog Scale, 26-item Short Form Health Survey, and the Chronic Pain Acceptance Questionnaire. Bittelbrunn et al [ 18 ] also highlighted the importance of mindfulness and pelvic floor physical therapy as important components of pelvic pain management, shown by improvements in pain catastrophizing and sexual function after treatment with these interventions in their meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, interventions involving brief mindfulness training and shared interpersonal narratives have demonstrated efficacy in managing endometriosis-related pain and restoring psychological stability (Moreira et al, 2022). Also, treatments like mindfulness-psychological intervention with practices involving conscious pelvic movement, breathing techniques and empathetic attention to painful areas have shown to reduce pain (Samami et al, 2023).…”
Section: Interoceptive-ecological Therapeutics In Autonomy and Commun...mentioning
confidence: 99%